PERANCANGAN KAWASAN WISATA BUDAYA JAWA TENGAH DI KOTA SALATIGA DENGAN KONSPE ARSITEKTUR VERNAKULAR - Alvin Yulianto; Dody Kurniawan; Karya Subagya (MAESTRO, 2021)
A Cultural Tourism Area is a type of activity developed in an area or sub-region of a tourist destination that relies on the richness of tourism in the form of objects and attractions of cultural tourism. To increase the love and passion for Central Javanese culture, a cultural tourism area is needed, where there is a place for batik education, culinary tours, as well as wayang kulit performances and training. Cultural Tourism also describes a tour based on the desire to add insight and life experience by visiting distinctive and unique tourist objects and attractions. The vernacular architectural approach can be used as a basic reference in the design of the Central Java Cultural Tourism Area in the City of Salatiga. The concept of this building is very suitable for use, the shape of the building is taken from the original traditional building form, but uses existing technologies.